2015
DOI: 10.1007/s00345-015-1635-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of de novo urge urinary incontinence after photoselective vaporization of the prostate

Abstract: Our data indicate that transient dnUUI occurs in a significant proportion of patients after PVP and it tends to decrease over time. Older-aged patients, patients with shorter time to Qmax, higher baseline storage symptom score, higher baseline total OABSS, smaller bladder volume at first desire to void, and smaller MCC may be prone to develop dnUUI postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…7,8,14 A recent study of Bae has shown that elderly patients with a higher baseline total overactive bladder symptom score, higher baseline storage symptom score, shorter time to Qmax, smaller bladder volume at first desire to void, and smaller maximum cystometric capacity on baseline urodynamics are more prone to develop transient incontinence. 21 No serious fatal complications occurred after 6-24 months of follow-up.…”
Section: Discussionmentioning
confidence: 87%
“…7,8,14 A recent study of Bae has shown that elderly patients with a higher baseline total overactive bladder symptom score, higher baseline storage symptom score, shorter time to Qmax, smaller bladder volume at first desire to void, and smaller maximum cystometric capacity on baseline urodynamics are more prone to develop transient incontinence. 21 No serious fatal complications occurred after 6-24 months of follow-up.…”
Section: Discussionmentioning
confidence: 87%
“…Age is an established risk factor for SUI at 1, 3, and 12 months after robot-assisted RP [ 12 ]. Similarly, increasing age is positively correlated with the occurrence of transient UI or SUI in transurethral vaporization of the prostate (TUVP), transurethral enucleation with bipolar (TUEB), or HoLEP [ 4 , 7 , 14 ]. Elevated BMI and enlarged prostate volume are also linked with postoperative SUI [ 15 ].…”
Section: Discussionmentioning
confidence: 99%